Improving the performance of construction industries for developing countries : programmes, initiatives, achievements and challenges - Rwelamila, Pantaleo; Aziz, Rashid Abdul (New York : Routledge, 2021)
"This book documents the experiences, development and prospects of t he construction industry in numerous developing countries"--
Construction industry development : general introduction / P.D. Rwel amila, Abdul-Rashid Abdul-Aziz.
Includes bibliographical references and index.
Keywords: Construction industry -- Developing countries; Building -- Developing countries